Editor for creating and applying computerise surveys - López Walle, Jeanette M.; Blanco Vega, Humberto; Ornelas Contreras, Martha; Tristán Rodríguez, José Leandro; Cocca, Armando; Mayorga Vega, Daniel; Viciana Ramírez, Jesús (2013)
The parallel development of the psychometric assessments and the computer technologies determined a big revolution regarding the construction and the application of psychological and educational tests. This report describes a computerized system that allows researchers to creating, applying, and tabulating surveys and paper instruments in an automatized way. Many studies describe the use of this tool, highlighting its main characteristics. This system can be considered a useful tool, since it permits to input data with higher precision and no need for previous codifications. Further, it allows researchers to know the latency period from the answer to each and every item. The prospects about new versions of the system stress on: extending the number of measured topics; creating automatic corrections systems; managing data via internet; and selecting the most valid items to measure each matter or specific groups of persons.